Issue Information. Issue 2 (17th June 2020) - Unknown
Abstract : Cover : In Barratt and Arkell (http://doi.org/10.1002/cpmo75 ), the image shows examples of WMISH results for gastrulation‐staged murine embryos. Lateral view of whole‐mount wild‐type murine embryos hybridized to riboprobes for A: Lhx1, B: Zic1 and C: Zic3 . (A ) Positive WMISH result with strong, clean signal in the expected tissues at 7.0 dpc. Tissues that do not express the target mRNA remain devoid of nonspecific background signal (black arrows). (B ) WMISH result for target that is not expressed at 7.25 dpc. There is no nonspecific background signal either. (C ) Riboprobe trapping in the lumen of a 7.75 dpc embryo, producing nonspecific background signal (white arrows). True target gene expression (white asterisk) is concealed by the trapping. Anterior is to the left in all images. Embryos were photographed in 100% glycerol and mounted on a microscope slide with coverslip